Reduction of doxorubicin resistance by tetrandrine and dauricine in harringtonine-resistant human leukemia (HL60) cells - He Qi-Yang; Meng Fan-Hong; Zhang Hong-Qing (Acta Pharmacologica Sinica, 2016)
AIM: To study whether tetrandrine (Tet) and dauricine (Dau) can reduce doxorubicin (Dox) resistance in the harringtonine (Har)-resistant human leukemia cells. METHODS: The drug cytotoxities were determined by counting cell numbers and colony formation. Cell cycle phases were assayed by flow cytometry, Dox contents were quantified by Dox fluorescence. RESULTS: The non-cytotoxic concentrations of Tet and Dau potentiated the growth-inhibitory actions of Dox in the Har-resistant HL60 cells. The colony formation effiencies were reduced from 60% by Dox to 0.2% by Tet + Dox and 9.2% by Dau + Dox. Retardation of the G2M phase cells was increased. But Tet and Dau did not potentiate Dox cytotoxities in the sensitive HL60 cells. Dox accumulation in the Har-resistant HL60 cells treated by Tet was increased. CONCLUSION: Dox resistance in the Har-resistant HL60 cells treated by Tet or Dau was reduced, due to the increase of Dox accumulation in the cells. One of the mechanisms of multidrug resistance in tumor cells is overexpression of cell membrane glycoproteins, termed P-glycoprotein (PGP). PGP pumps antitumor drugs out of tumor cells, causing drug resistance. Calcium antagonists and some calmodulin inhibitors such as verapamil, nifedepine, trifluorapine have effect on reversion of drug resistance, binding directly to PGP, but side effect of them is intolerable in clinical use. So searching for other potentiators to overcome drug resistance may be another avenue. Tetrandrine (Tet) effectively circumvented the resistance of Chinese hamster ovary cells to doxorubicin (Dox). Dauricine (Dau) is a bisbenzylisoquinoline alkaloid from Stephaia tetrandra. In this paper we studied whether Tet and Dau could reduce Dox resistance in the harringtonine (Har)-resistant human leukemia 60 (HL60) cells.